Bilingual language processing relies on shared semantic representations that are modulated by each language - Catherine Chen; Xue L. Gong; Christine Tseng; Daniel L. Klein; Jack L. Gallant; Fatma Deniz (Proceedings of the National Academy of Sciences, 2026)
Billions of people throughout the world are bilingual, and they can extract meaning from multiple languages. While some evidence suggests that there is a shared system in the human brain for processing semantic information from native and non-native languages, other evidence suggests that semantic processing is language specific. We conducted a study to determine how semantic information for different languages is represented in the brains of bilinguals. Functional magnetic resonance imaging (fMRI) was used to record brain responses while participants read several hours of natural narratives in their native (Chinese) and non-native (English) languages. These data were then used to compare semantic representations between the two languages. We find that semantic representations are largely shared between languages, while there are fine-grained differences in the representation of some semantic categories across languages. These results reconcile current competing theories of bilingual language processing.